The Role of Chinese Herbal Therapy in Methamphetamine Abuse and its Induced Psychiatric Symptoms - Chen, Lin; Ru, Qin; Xiong, Qi; Zhou, Mei; Yue, Kai; Wu, Yuxiang (Frontiers in Pharmacology, 2021)
Repeated intake of METH leads to drug addiction, inability to limit intake, and intense drug cravings. It is also likely to cause psychiatric impairment, such as cognitive impairment, depression, anxiety and so on. Because of the involved specific neurobiological mechanisms are complex and have not been fully and systematically elucidated, so far, there is no established pharmacotherapy for METH abuse. Studies have found that a variety of Chinese herbal medicines have significant therapeutic effects on psychiatric symptoms and have the advantages of multi-target comprehensive treatment. We conducted a systematic review, from neurobiological mechanisms to candidate Chinese herbal medicines, hoping to provide new perspectives and ideas for the prevention and treatment of METH abuse.